Absorption, distribution, metabolism, and excretion of ticagrelor in healthy subjects - Teng, Renli; Oliver, Stuart; Hayes, Martin A; Butler, Kathleen (Drug metabolism and disposition, 2010)
Ticagrelor [(1S,2S,3R,5S)-3-[7-[[(1R,2S)-2-(3,4-difluorophenyl) cyclopropyl]amino]-5-(propylthio)-3H-1,2,3-triazolo[4,5-d]pyrimidin-3-yl]-5-(2-hydroxyethoxy)-1,2-cyclopentanediol)] is a reversibly binding oral P2Y(12) receptor antagonist in development for the prevention of thrombotic events in patients with acute coronary syndromes. The pharmacokinetics, metabolism, and excretion of ticagrelor were investigated over 168 h in six healthy male subjects receiving a single oral suspension dose of 200 mg of [(14)C]ticagrelor. Ticagrelor was rapidly absorbed with a maximum plasma concentration at 1.5 h. The major active metabolite, AR-C124910XX, is formed by O-deethylation. Exposure to AR-C124910XX was 29% of peak and 40% of overall exposure to ticagrelor. In most subjects, radioactivity was undetectable in plasma after 20 h and whole blood after 12 h (half-life values of 6.3 and 4.6 h, respectively). The ratio of radioactivity in plasma to whole blood was 1.69, suggesting that ticagrelor and its metabolites are largely restricted to the plasma space. Mean radioactivity recovery was 26.5% in urine and 57.8% in feces. Major circulating components in the plasma and feces were identified as ticagrelor and AR-C124910XX, whereas in urine the major components were metabolite M5 (AR-C133913XX) and its glucuronide conjugate M4. Levels of unchanged ticagrelor and AR-C124910XX were <0.05% in the urine, indicating that renal clearance of ticagrelor and AR-C124910XX is of minor importance. Interindividual variability was small in both urine and fecal extracts with only small quantitative differences. All 10 of the metabolites were fully or partially characterized and a full biotransformation pathway was proposed for ticagrelor, in which oxidative loss of the hydroxyethyl side chain from ticagrelor forms AR-C124910XX and a second oxidative pathway leads to N-dealkylation of ticagrelor, forming AR-C133913XX.